Maternal Depression in Early Childhood and Developmental Vulnerability at School Entry - Wall-Wieler, Elizabeth; Roos, Leslie L.; Gotlib, Ian (International Journal of Population Data Science, 2020)
Introduction Studies on the relationship between exposure to maternal depression in early childhood and childhood development have been limited by small samples, lack of information on timing of maternal depression, and use of a composite measure of childhood development. Objectives and Approach We linked multiple Manitoba datasets to examine the relationship between exposure to maternal depression in early childhood and childhood development at school entry across five domains, and age at exposure to maternal depression on developmental outcomes using a population-based cohort (n = 52,103). Maternal depression was defined using physician visits, hospitalizations, and pharmaceutical data, while developmental vulnerability was assessed using the well-validated Early Development Instrument. Relative risk of developmental vulnerability was assessed using log-binomial regression models, adjusted for maternal and childhood characteristics at the birth of the child. Results Children exposed to maternal depression before age 5 had a 17% higher risk of having at least one developmental vulnerability at school entry than children not exposed to such depression before age 5. Exposure to maternal depression before age 5 was most strongly associated with social competence (aRR = 1.28, 95% CI 1.20, 1.38), physical health and well-being (aRR = 1.28, 95% CI 1.20, 1.36), and emotional maturity (aRR = 1.27, 95% CI 1.18, 1.37). For most developmental domains, exposure to maternal depression before age 1 and between ages 4 and 5 had the greatest association with developmental vulnerability. Conclusion / Implications Our findings that children exposed to maternal depression were at higher risk of developmental vulnerability at school entry is consistent with previous studies. However, we found that the association between exposure to maternal depression and development varied across developmental domains, and the relationship varied depending on the age of exposure to maternal depression. Ongoing analyses of discordant cousins will shed more light on the causal nature of this relationship.